Catholicism-Hinduism: Vedantic Investigation of Raimundo Panlkkar's Attempt to Bridge Building, - Kadankavil, Thomas (Journal of Dharma, 1988)
Kana Mitra, Catholicism-Hinduism: Vedantic Investigation of Raimundo Panlkkar's Attempt to Bridge Building, Lantian, University Press, pp. 186.